Massive targeting of liposomes, surface-modified with anionized albumins, to hepatic endothelial cells - Kamps, Jan A. A. M. (The National Academy of Sciences of the USA, 1997)
Human serum albumin (HSA) derivatized with cis-aconitic anhydride was covalently coupled to liposomes with a size of approximately 100 nm [polyaconitylated HSA (Aco-HSA) liposomes]. Within 30 min after injection into a rat, Aco-HSA liposomes were completely cleared from the blood and almost exclusively taken up by the liver, whereas in control liposomes 80% was still present in the blood at that time. Endothelial cells were shown to account for almost two-thirds of the hepatic uptake of the Aco-HSA liposomes, the remainder being recovered mainly in the liver macrophages (Kupffer cells). With fluorescently labeled liposomes it was shown that the Aco-HSA liposomes target a vast majority (>85%) of the cells in the endothelial cell population. Control liposomes were not taken up to a significant extent by the endothelial cells. Uptake of Aco-HSA liposomes by both endothelial and Kupffer cells was inhibited by preinjection with polyinosinic acid, indicating the involvement of scavenger receptors in the uptake process. The uptake of Aco-HSA liposomes by liver endothelial cells was dependent on liposome size; with increasing liposome diameter endothelial cell uptake decreased in favor of Kupffer cell uptake. We have demonstrated that massive in vivo targeting of liposomes to a defined cell population other than macrophages is possible. Aco-HSA liposomes thus may represent an attractive drug carrier system for treatment of various liver or liver endothelium-associated disorders.